2008
DOI: 10.1037/0736-9735.25.3.499
|View full text |Cite
|
Sign up to set email alerts
|

The Mothers and Toddlers Program: Preliminary findings from an attachment-based parenting intervention for substance-abusing mothers.

Abstract: The authors examined pilot data from an attachment-based parenting intervention for substance-abusing mothers of toddlers (ages 12–36 months). The Mothers and Toddlers Program (MTP) is a 20-week individual therapy intervention that aims to help mothers develop more balanced representations of their children and improve their capacity for reflective functioning (i.e., recognition of the intentional nature of children’s behavior). The authors hypothesized that improvement in maternal representational balance and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
159
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(171 citation statements)
references
References 30 publications
9
159
0
3
Order By: Relevance
“…This type of approach has been effective with mothers struggling with substance use issues and aggression (Slade et al, 2005, Suchman et al, 2008, Toth et al, 2002. Fathers in this sample clearly lacked reflective skills indicating an inability to not only discuss their own emotions and thoughts, but also a limited and often non-existent capacity to think about the emotional experiences of their children.…”
Section: Discussionmentioning
confidence: 99%
“…This type of approach has been effective with mothers struggling with substance use issues and aggression (Slade et al, 2005, Suchman et al, 2008, Toth et al, 2002. Fathers in this sample clearly lacked reflective skills indicating an inability to not only discuss their own emotions and thoughts, but also a limited and often non-existent capacity to think about the emotional experiences of their children.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional substance abuse treatments focus almost exclusively on parents' substance use, rather than on improving parent-young child interactions and/or young child adjustment (12). Evidence-based parenting interventions are a critical adjunctive treatment given that the young children of parents who are substance-involved are at such high risk for a variety of adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, models of mammalian behavior suggested that dopamine, along with other biological mechanisms, activates the neural pathways necessary for parents' motivation to bond with, nurture, and protect offspring, with these parenting behaviors shaping offspring neural and social development (11). Given these mammalian models, it may be that craving substances competes with and impedes substance-involved parents' capacity for positive caregiving (12). Further, repeated exposure to addictive substances likely reduces parents' dopaminergic response to stress, resulting in vulnerability to negative emotions and extreme distress when caring for distressed children.…”
Section: Neurobiology Of Parenting and Substance Usementioning
confidence: 99%
See 2 more Smart Citations